The References of Using Deixis in the Novel The Kite Runner - Ika Novia Sri Haryanti; Wahyuni Wahyuni; Waladdin Panggabean (Prologue: Journal on Language and Literature, 2020)
There are two objectives of this research; to identify the types of deixis used in the utterances in the novel The Kite Runner; and to explain the references of using deixis found in the novel. The method used in this research is the qualitative descriptive method because the data were analyzed in the form of words and utterances. The theory used in this research is the Deixis theory by Stephen C. Levinson’s, also supported by the theory of references by Yule. The result of this research shows that there are five types of deixis found in the novel The Kite Runner by Khaled Hosseini, those are person deixis, place deixis, time deixis, discourse deixis, and social deixis. The references of using deixis found anaphora and cataphora. Based on the data deixis that has been found and analyzed by the researcher in this research, person deixis is more dominant used in the novel, and for the use of references, anaphora reference is more dominant used than cataphora reference in the novel The Kite Runner.